Theoretical elements of veterinary therapeutics - Cristina, T. Romeo.; Schmerold, I.,; Tuns, I. C. (Medicamentul Veterinar)
The present essay describes, logically and in a synthetic way, the main elements of veterinary therapeutics. The first part refers to the concept of dose and the main factors affecting its establishment, presenting the elements related to: weight and body surface area, the therapeutic range, animal’s size, genetic factors, specific variations, digestive tract’s anatomy, factors related to age, sex, pregnancy, time of administration, tolerance and intolerance to medications, and factors that may influence response to the medication (diminished/amplified response, dose administrations’ toxicity, etc.). Following are revealed the key factors that determine the administration’s, frequency like: drug’s cleareance,drug’s concentration, administration rate, repeated-dose effect and the frequency establishing, etc. There are no missing also the elements that are describing: the plateau effect, zero-order kinetics, drug residues effect, the dose-effect relationship, the first-pass effect, latency and intensity, the risk-benefit ratio in the veterinary therapy, to full understanding of the concepts by the vet practicians.